Corpo-fitness e Instagram: um corpo suficientemente bom? - Morais, Isabella Cláudia Koga (2018)
The use of the body has long served to anatomy and physiology, the subject was put on hold, in the initial attempt of psychoanalysis to return it to the body ends up discarding this last one, except Winnicott, who rescues them from the psyche-soma reading of human nature. We enter the body-subject of postmodernity, body seen as a place of social symbols, fissures, spectacle and total erasure, notwithstanding body of health care and body aesthetics, body-fitness contextualizing itself through technological changes, cyber world, of social networks. Starting from these readings the objective of this research was to understand how the body-fitness generated subjectivity and how it is produced in its relations with photography and social network Instagram, from qualitative investigation in regard to the psychoanalytic research with the interview technique centered on the following triggers: body, body-fitness and Instagram. 13 individuals were interviewed separately, men and women over 18, who had a public profile on the Instagram and practiced physical activity. The interviews were recorded in audio and later transcribed, backing up the ethical considerations. The analyzes were based on the directed reading through the listening and the transference of the researcher to the text of the participants of the research. Six themes were set up: Body incarnate, Body time and space, From the omnipotent body to good enough, Cyberbody and From the body good enough to the sufficiency of labor care. It was found that the body, even without its fitness and bodybuilder configurations, occupies fundamental place in human existence, the reading from the psyche-soma seems pertinent; even if there is no consensus of body-fitness definitions and bodybuilder suggests there is a metaphor that unites them, of man's need to remain in the world feeling really alive; and going towards the writers who discuss the body-subject postmodern society social networks allow a different way of the psyche-soma being in the world. Thus it is questioned where the mother is and the body is involved as environment, body good enough; as well as emphasizing the need for studies that explore and deepen man within the cyber-technological context of social networks.